2019
DOI: 10.1289/ehp3431
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Some Light in the Dark—A Comparison of Personal Measurements with Satellite-Based Estimates of Exposure to Light at Night among Children in the Netherlands

Abstract: Background:Exposure to light at night (LAN) can perturb the biological clock and affect sleep and health. Previous epidemiological studies have evaluated LAN levels measured by satellites, but the validity of this measure as a proxy for personal LAN exposure is unclear. In addition, outdoor satellite-measured LAN levels are higher in urban environments, which means that this measure could potentially represent a proxy for other, likely urban, environmental exposures.Objectives:We evaluated correlations of sate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…Studies using images with higher resolution and multi-spectral bands taken from the ISS demonstrated that exposure to the blue-light spectrum of outdoor artificial light at night appeared to have stronger effects on hormone-dependent cancer incidence (i.e., prostate and breast cancers) compared to the green-light and red-light spectrums [205,206]. Using VIIRS/DNB images and ISS photos of outdoor light, a comparison of personal measurements with satellite-based estimates of exposure to night light found a discrepancy between outdoor NTL and indoor light exposure [207], indicating that the modifying factors should be used when using the satellite NTL to evaluate potential effects of night light on human health. Such findings can help make better policies for minimizing the adverse health effects of artificial light exposure on human health.…”
Section: Light Pollution and Associated Effectsmentioning
confidence: 99%
“…Studies using images with higher resolution and multi-spectral bands taken from the ISS demonstrated that exposure to the blue-light spectrum of outdoor artificial light at night appeared to have stronger effects on hormone-dependent cancer incidence (i.e., prostate and breast cancers) compared to the green-light and red-light spectrums [205,206]. Using VIIRS/DNB images and ISS photos of outdoor light, a comparison of personal measurements with satellite-based estimates of exposure to night light found a discrepancy between outdoor NTL and indoor light exposure [207], indicating that the modifying factors should be used when using the satellite NTL to evaluate potential effects of night light on human health. Such findings can help make better policies for minimizing the adverse health effects of artificial light exposure on human health.…”
Section: Light Pollution and Associated Effectsmentioning
confidence: 99%
“…However, these levels were not correlated with measured bedroom light levels in evening or nighttime [28,29]. And there is only a weak correlation between satellite-measured ALAN and outdoor light levels [28]. These studies suggest that the significant association of ALAN with breast cancer in general population should not be interpreted as a direct ALAN risk in breast cancer.…”
mentioning
confidence: 75%
“…These studies all used satellite-measured ALAN levels to determine exposure. However, these levels were not correlated with measured bedroom light levels in evening or nighttime [28,29]. And there is only a weak correlation between satellite-measured ALAN and outdoor light levels [28].…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Constant light (CL) was an extremity of prolonged light exposure, which may occur naturally or artificially. Due to light pollution in public and private areas, constant light is a major part of people's lives quietly without attracting notice (Huss et al, 2019;Park et al, 2019). Constant light exposure was able to influence people's behavior and health, making adverse effects on the cardiovascular system reportedly (Furlan et al, 2000;Chang et al, 2015;Reynolds et al, 2017;Benedetto and Contin, 2019;Bohmer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%